Hubungan kepuasan kerja dengan prestasi kerja di kalangan pekerja-pekerja Perbadanan Kemajuan Perusahaan Kayu Sarawak (PUSAKA), Kuching, Sarawak - Rahim, Bin Ibas. (1997)
The purpose of this styudy was to determine job satisfaction factors among workers of the Sarawak Timber Industry Development Corporation (STIDC), Kuching, Sarawak and their relationships with job performance. Ten demographic characteristics: gender, age, martial, training related job, job experience, how to come to work, number of children, and total monthly income were selected for study. The job satisfaction factors of this study were work situation, pay, promotion, supervisor, co-workers, and fringe benefits. Job performance was seen from aspects of attending work, working on time, job discipline, quality of output and willing ness to work after overtime.